"Women and the environmental are together": using Participatory Rural Appraisal to examine gendered tensions about the environment. Issue 6 (3rd July 2017) - Quigley, Cassie F.; Che, S. Megan; Achieng, Stella; Liaram, Sarah
Abstract : Environmental education research (EER) rarely includes women's perspectives. This means that in environmental education research, an entire knowledge source is largely ignored. This study employed a methodology called Participatory Rural Appraisal, a methodology new to the field of EER, of Kenyan teachers from the Maasai Mara region to understand the tensions around environmental views. The purpose of this work was to examine, through the use of a participatory methodology, the conceptions of the environmental of these teachers and to uncover gendered tensions. The analysis included a continuous, thematic review that included the participants during the analysis. The findings included the following themes: Why are people doing what they are doing? Who is or is not acting? How do we move forward? This research documented gendered tensions such as the burdens of responsibility, the power imbalance disadvantaged women feel regarding solving environmental issues, and the blame that is directed at both men and women as a result of these burdens and power imbalances. This methodology provided a way for participants to understand each other's viewpoints in layered ways, and pointed to gender issues throughout that sometimes caused blame. However, it also helped the participants think about how to work together.